1973
DOI: 10.1002/eji.1830030306
|View full text |Cite
|
Sign up to set email alerts
|

The extent of diversity of anti‐hapten antibodies in inbred mice: anti‐NIP (4‐hydroxy‐5‐iodo‐3‐nitro‐phenacetyl) antibodies in CBA/H mice

Abstract: The number of different anti-NIP (4-hydroxy-5-iodo-3-nitro-phenacetyl) molecules which inbred CBA/H mice can make was estimated. Spleen cell transfer has been used and the isoelectric spectra of antibodies present in the sera of recipient mice determined. Comparison between the sets of monoclonal antibody spectra deriving from different donor mice gave a repeat frequency for individual spectra. This frequency permitted a statistical estimate (see Addendum) of the minimum number of different anti-NIP molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 14 publications
5
40
0
Order By: Relevance
“…The estimate of purity made in this way is in excellent agreement with the estimate from the fingerprint studies. Half maximal competition was reached at an RNA to DNA ratio of 1 Using a mouse K-chain mRNA preparation of unknown purity, Delovitch and Baglioni (24) observed a biphasic Cot curve which, to a certain extent, is similar to ours. They also ignored the existence of the external section of the mRNA and assumed that the reiterated fraction represented "subclass" specific sequences.…”
Section: Hybridization Kineticssupporting
confidence: 80%
See 1 more Smart Citation
“…The estimate of purity made in this way is in excellent agreement with the estimate from the fingerprint studies. Half maximal competition was reached at an RNA to DNA ratio of 1 Using a mouse K-chain mRNA preparation of unknown purity, Delovitch and Baglioni (24) observed a biphasic Cot curve which, to a certain extent, is similar to ours. They also ignored the existence of the external section of the mRNA and assumed that the reiterated fraction represented "subclass" specific sequences.…”
Section: Hybridization Kineticssupporting
confidence: 80%
“…One inbred strain of mice has been shown to be capable of producing eight thousand different antibody molecules against the hapten NIP (4-hydroxy-5-iodo-3-nitrophenacetyl) (1). Another inbred mouse strain was shown to produce many different antibody molecules against DNP (dinitrophenyl), of which more than 500 crossreact strongly with TNP (trinitrophenyl) (2).…”
mentioning
confidence: 99%
“…Although responses in mice to certain antigenic determinants may invariably include a "dominant" clonotype (15-17), a study by Kreth and Williamson has indicated that the immune response of CBA/H mice to the 4-hydroxy-5-iodo-3-nitrophenylacetyl (NIP) determinant may involve as many as 3,000-30,000 distinct clonotypes (18) . Given such an enormous array of clonotypes in the adult mouse potentially available for responsiveness to determinants such as NIP and probably to DNP as well, the analysis of the generation of the specificity repertoire to these determinants is extremely hampered .…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments measuring the number of nitro-iodohydroxy-phenacetyl-binding antibodies which can be made in CBA/H mice indicated a minimum number of 70 VH-genes and 70 VL-genes are required if all of the information is carried in the germ-line (19). This number would be comfortably contained in a VH-pOO1 of 5000 genes.…”
Section: Discussionmentioning
confidence: 99%